2014
DOI: 10.1080/09712119.2014.978773
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and quality characteristics of flaxseed-fed broiler chicks

Abstract: A 42-day study was conducted to evaluate the effect of ground full-fat flaxseed supplementation on growth performance, carcass characteristics, α-linolenic acid (ALA), linoleic acid (LA) and organoleptic characteristics of broiler meat. A total of 200 one-day-old broiler chicks were randomly allocated to five experimental groups and were fed isoenergetic and isonitrogenous diets containing flaxseed at 0%, 2.5%, 5.0%, 7.5% and 10%. Flaxseed supplementation did not affect the weekly body weight of broiler chicks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
23
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 28 publications
11
23
2
Order By: Relevance
“…Nonetheless, the FCR and percentage mortality were not affected by dietary treatments. A similar decrease in FI and BWG with no significant effect on mortality has been reported following the supplementation of chia seed, [ 7 ] Camelina seed, [ 40 ] and flaxseed [ 23,41 ] in broiler chickens. In addition, the supplementation of Camelina seed [ 12 ] and extruded flaxseed [ 42 ] did not affect FCR in broiler chickens.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Nonetheless, the FCR and percentage mortality were not affected by dietary treatments. A similar decrease in FI and BWG with no significant effect on mortality has been reported following the supplementation of chia seed, [ 7 ] Camelina seed, [ 40 ] and flaxseed [ 23,41 ] in broiler chickens. In addition, the supplementation of Camelina seed [ 12 ] and extruded flaxseed [ 42 ] did not affect FCR in broiler chickens.…”
Section: Discussionsupporting
confidence: 62%
“…Similarly, dietary flaxseed did not affect carcass and meat yields in broiler chickens. [ 6,41 ] The supplementation of TCSM induced a dose‐dependent reduction in abdominal fat and fat percentage in breast and thigh muscles of broiler chickens. This observation is consistent with the reduction in serum triglycerides and total cholesterol in the TCSM‐supplemented birds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The nonsignificant effect of flaxseed on sensory characteristics has also been reported and is similar to our study's findings (26). However, in contrast, there is a study that reported a significant reduction in the aroma, flavor, taste, and overall acceptability of nugget meat from chickens fed with increasing levels of dietary flaxseed (17).…”
Section: Discussioncontrasting
confidence: 48%